Trajectories of Platform-mediated Gig Work in Nordic Taxi and Food Delivery Industries - Sigurd M. N. Oppegaard; Johan Alfonsson; Stine Rasmussen; Jere Immonen (Nordic Journal of Working Life Studies)
While the Nordic labor market model is renowned for providing ‘good’ jobs, we have over the last decade nonetheless seen the rise of platform-mediated gig work, associated with relatively precarious working conditions, in the Nordic countries. Analyzing the emergence and development of platform-mediated gig work in the taxi and food delivery industries in Denmark, Finland, Norway, and Sweden, this article identifies four trajectories: Evasion, disruption, adaption, and market exit. It shows that gig platforms established themselves in the ‘fringes’ of the Nordic labor market model, evaded regulations by classifying workers as self-employed contractors, recruited workers from marginalized segments of the labor force, and provoked regulatory responses that deregulated markets to facilitate their business model. The analysis thus highlights the importance of product market regulations in shaping the development of platform-mediated gig work and emphasizes the segmented nature of the Nordic labor market model.